Cardiac remodeling and urinary nag levels in patients with CHF of ischemic origin - Lysenko, V.; Syvolap, V.; Лисенко, Владислав Андрійович; Сиволап, Віталій Вікторович (Санкт-Петербург: ЛИТ А, 2021)
The relationship between cardiac remodeling in patients with CHF with glomerular-tubular changes in the kidneys is still insufficiently studied, and the question of the relationship of urinary NAG with parameters of cardiac remodeling remains open. The Aim: To investigate the relationship between the biomarker of tubulo-interstitium NAG in urine with parameters of cardiac remodeling in patients with CHF of ischemicorigin.Materials and methods. The study enrolled 50 patients with CHF of ischemic origin II-IV FC. Patients were divided into 2 groups depending on the concentration of NAG. In the first group (n=29) the NAG concentration was greater than 37.7 ng/ml, in the second (n=21)-less than 37.7 ng/ml. Patients with CHF of ischemic origin without and with tubulo-interstitial injury (according to the concentration of NAG in urine) probably didn’t differ in age (p=0,201), height (p=0,246), weight (p=0,690), body surface area (p=0.071). All patients underwent Doppler echocardiography on a device "Esaote MyLab Eight" (Italy) and enzyme-linked immunosorbent assay for urinary NAG (SEA 069 Hu, Cloud-Clone Corp., USA), sensitivity <0.54 ng/ml.Results.The mean urine concentration of NAG in the first group was 48 (46; 88) ng/ml, in the second group -22 (16; 29) ng/ml. Groups of the CHF patients with elevated and normal levels of urinary NAG didn’t differ statistically in creatinine (0.110±0.023 mmol/l vs. 0.110±0.018 mmol/l (p=0.883)); glomerular filtration rate by CKD-EPI (p=0.791), MDRD (p=0.976), and Cockcroft-Gault (p=0.054), linear and volumetric parameters of the left and right ventricles, left atrium, wall thickness, and myocardial mass index, types of LV geometry, parameters of systolic and diastolic LV function. The vast majorityof patients in both groups had eccentric hypertrophy (69% vs. 62%; p=0.608) and diastolic dysfunction by type of relaxation disorder (45% vs. 57%; p=0.406).Conclusion.There are no significant changes in the structure and function of the heart in patients with CHF of ischemic origin associated with changes in the concentration of urinary NAG. Urinary NAG didn’t show associative pathogenetic links with cardiac remodeling in patients with CHFof ischemic origin.
Keywords: Cardiac remodeling; Chronic Heart Failure; urinary NAG; Cardiorenal syndrome; diastolic dysfunction